Teaching “like you do at home” or “like you’re in a different place”? : Two prominent stances on teaching across borders expressed by academic migrants in Thailand (Comparative & International Education Series, 2021)
Building on studies which examine academic migrants’ teaching experiences, this chapter explores two common stances occupied by those who teach across borders: teach like you do at home and teach like you’re in a different place. This chapter explores these stances by considering the accounts of 25 academic migrants working in Thailand. First, we consider teach like you do at home. This idea was present across our dataset, and is connected to flows of knowledge, skills, and prestige, as well as often unreflexive assumptions about Northern epistemic and pedagogic superiority. Next, we consider teach like you're in a different place, or the idea that teaching and learning is inevitably contextual. The chapter argues that teaching across borders involves a meeting of teachers, learners, and knowledges in a particular time/place. We conclude by offering reflective statements for academic migrants to consider about teaching overseas and meeting learners where they are.